Emerging cooperativity between Oct4 and Sox2 governs the pluripotency network in early mouse embryos - Yanlin Hou; Zhengwen Nie; Qi Jiang; Sergiy Velychko; Sandra Heising; Ivan Bedzhov; Guangming Wu; Kenjiro Adachi; Hans R Scholer (eLife, 2025)
During the first lineage segregation, mammalian embryos generate the inner cell mass (ICM) and trophectoderm (TE). ICM gives rise to the epiblast (EPI) that forms all cell types of the body, an ability referred to as pluripotency. The molecular mechanisms that induce pluripotency in embryos remain incompletely elucidated. Using knockout (KO) mouse models in conjunction with low-input ATAC-seq and RNA-seq, we found that Oct4 and Sox2 gradually come into play in the early ICM, coinciding with the initiation of Sox2 expression. Oct4 and Sox2 activate the pluripotency-related genes through the putative OCT-SOX enhancers in the early ICM. Furthermore, we observed a substantial reorganization of chromatin landscape and transcriptome from the morula to the early ICM stages, which was partially driven by Oct4 and Sox2, highlighting their pivotal role in promoting the developmental trajectory toward the ICM. Our study provides new insights into the establishment of the pluripotency network in mouse preimplantation embryos.